2007
DOI: 10.1179/174313107x189212
|View full text |Cite
|
Sign up to set email alerts
|

Automatic number plate information extraction and recognition for intelligent transportation system

Abstract: In this paper, a new license plate information retrieval system is designed and developed. The system has two main modules: segmentation and recognition. In segmentation, interested information on the image is extracted through the processes of Kaiser resizing, morphological filtering, artificial shifting and bi-directional vertical thresholding. In recognition module, a novel approach for principal component analysis (PCA) and fast backpropagation neural net composition is used as a recognizer. The novel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The introduced method worked effectively under light variations and even under shadow. Cinsdikici et al [15] suggested a new information retrieval system of number plate recognition. The suggested method was a combination of two major steps namely, character segmentation and number recognition.…”
Section: Related Workmentioning
confidence: 99%
“…The introduced method worked effectively under light variations and even under shadow. Cinsdikici et al [15] suggested a new information retrieval system of number plate recognition. The suggested method was a combination of two major steps namely, character segmentation and number recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Thirdly the histogram of brightness was shifted by | − |. Consequently, the drift coefficients and were calculated, using (9), where the two regions were separated by the brightness baseline.…”
Section: Real-time Brightness Feedbackmentioning
confidence: 99%
“…The authors in [8] used normalization for local luminance to eliminate the impact of light changes so as to achieve the automatic detection and recognition of signs in natural scenes. In [9,10], studies on license plate images in natural scenes were performed by means of histogram equalization and tensile contrast. In [11], Tan et al employed the combination of high frequency enhancement and neural networks to strengthen the contrast in van images under different light conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The images acquired from both the visible light charge coupled device (CCD) and infrared CCD can be processed by computer vision, which is real-time and reliable and can work online. Online detection by computer vision have been wildly used in many fields, such as fire detection by visible light camera [10] and infrared vision [11], number plate detection [12], railway safety [13] and driver assistance [14].…”
Section: Introductionmentioning
confidence: 99%